Proactively Building Capabilities for the Post-Acquisition Integration of Information Systems - Peter J. Wynne (Copenhagen Business School (CBS), 2019)
To gain the strategic benefits of acquisitions, firms must successfully execute post-acquisition IS integration. Unfortunately, a key reason acquisitions regularly fail is because firms fail to successfully leverage the post-acquisition IS integration capability. This capability is not found in non-acquisitive firms. Although research has shown that this capability must be built during the years preceding an acquisition, it has not comprehensively explained what the capability is, nor how it is proactively developed. Through an engaged scholarship learning partnership, this PhD examines how Maersk, proactively built their post-acquisition IS integration capability prior to their first acquisition. By adopting the resource-based view and its extension into dynamic capabilities this PhD contributes mid-range theory that describes and explains this proactive capability building process. Firms can leverage this useful knowledge when building their own IS integration capability to become capable of executing post-acquisition IS integration.
hdl:10398/9705
Keywords: 650